Contemporary Quantitative Finance Essays in Honour of Eckhard Platen - Chiarella, Carl.; Novikov, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The contributors to this volume write a series of articles outlining contemporary advances in a number of key areas of mathematical finance such as, optimal control theory applied to finance, interest rate models, credit risk and credit derivatives, use of alternative stochastic processes, numerical solution of equations of mathematical finance, estimation of stochastic processes in finance. The list of authors includes many of the researchers who have made the major contributions to these various areas of mathematical finance. This volume addresses both researchers and professionals in financial institutions, as well as regulators working in the above mentioned fields.
Probabilistic Aspects of Arbitrage -- Finitely Additive Probabilities and the Fundamental Theorem of Asset Pricing -- M6$1 (BOn Minimal Market Models and Minimal Martingale Measures -- The Economic Plausibility of Strict Local Martingales in Financial Modelling -- A Remarkable ?-finite Measure Associated with Last Passage Times and Penalisation Problems -- Pricing Without Equivalent Martingale Measures Under Complete and Incomplete Observation -- Existence and Non-uniqueness of Solutions for BSDE -- Comparison Theorems for Finite State Backward Stochastic Differential Equations -- Results on Numerics for FBSDE with Drivers of Quadratic Growth -- Variance Swap Portfolio Theory -- Stochastic Partial Differential Equations and Portfolio Choice -- Issuers$1 (BCommitments Would Add More Value than Any Rating Scheme Could Ever Do -- Pricing and Hedging of CDOs: A Top Down Approach -- Constructing Random Times with Given Survival Processes and Applications to Valuation of Credit Derivatives -- Representation of American Option Prices Under Heston Stochastic Volatility Dynamics Using Integral Transforms -- Buy Low and Sell High -- Continuity Theorems in Boundary Crossing Problems for Diffusion Processes -- Binomial Models for Interest Rates -- Lognormal Forward Market Model (LFM) Volatility Function Approximation -- Maximum Likelihood Estimation for Integrated Diffusion Processes.s
Keywords: Mathematics; Finance; Numerical analysis; Mathematical optimization; Distribution (Probability theory).; Economics -- Statistics; Mathematics; Quantitative Finance; Calculus of Variations and Optimal Control; Optimization; Probability Theory and Stochastic Processes; Statistics for Business/Economics/Mathematical Finance/Insurance.; Numerical Analysis